2011
DOI: 10.2478/s11686-011-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

A survey of larval digeneans in the commonest intertidal snails from Northern Patagonian coast, Argentina

Abstract: Over a two-years period, a survey was carried out in order to increase the knowledge of digeneans parasitising the commonest intertidal gastropods on the Patagonian coast, Southwestern Atlantic Ocean. A total of 4,725 gastropods were examined. Six species of digenean parasitising four snail species were found; four of them were registered for first time: Maritrema sp. 1 (Microphallidae) in Crepidula dilatata (Calyptraeidae), Parorchis sp. (Philophtalmidae) and sporocyst of Renicolidae in Trophon geversianus (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 40 publications
0
34
0
8
Order By: Relevance
“…This finding could be explained by the high abundance of grapsid crabs-the second-intermediate hosts of the microphallid species (Alda et al 2011a), except for M. simillimus-along with the high diversity of gulls (Petracci and Delhey 2005). Microphallids also prevail in the intertidal gastropods from the Patagonian coast in Argentina (Gilardoni et al 2011) and in the rissooids of the European coast (Deblock 1980, Kube et al 2002, Skirnisoon et al 2004, Thieltges et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained by the high abundance of grapsid crabs-the second-intermediate hosts of the microphallid species (Alda et al 2011a), except for M. simillimus-along with the high diversity of gulls (Petracci and Delhey 2005). Microphallids also prevail in the intertidal gastropods from the Patagonian coast in Argentina (Gilardoni et al 2011) and in the rissooids of the European coast (Deblock 1980, Kube et al 2002, Skirnisoon et al 2004, Thieltges et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…For each studied species, comparisons with other available sequences of the same family were made using NCBI BLAST (https://blast.ncbi.nlm.nih.gov/) to support the morphological diagnosis. A microphallid species parasitizing C. dilatata was previously described by Gilardoni et al (2011) and erroneously identified as Maritrema sp. 1; however, comparison of molecular data with NCBI BLAST indicated that the sequence showed low similarity with other species of the genus Maritrema (69-77% in ITS1 and 83-86% in ITS2).…”
Section: Methodsmentioning
confidence: 99%
“…2) in a survey of larval digeneans in the intertidal snails from the northern Patagonian coast. Gilardoni et al (2011) suggest that sporocysts and cercariae of Maritrema sp. 2 from the gastropod Siphonaria lessoni (Blainville) probably correspond to M. madrynense.…”
Section: Remarksmentioning
confidence: 99%
“…nov.) were found in the study area, and also two different species were identified as larval stages in the same area, it is probable that Maritrema sp. 1 registered by Gilardoni et al (2011) from Crepipatella dilatata Lamarck, corresponds to M. formicae sp. nov.…”
Section: Remarksmentioning
confidence: 99%
See 1 more Smart Citation